Teaching visual literacy in the secondary English/language arts classroom: an exploration of teachers’ attitudes, understanding and application - Robertson, Martha S.M. (Kansas State University, 2007)
With changes in technology over the past decades, literacy now requires receiving and transmitting information using various, multiple media. Recognizing the need for students to be literate in more the traditional areas of reading and writing, professional organizations and states have set standards for English/language arts related to non-print literacy, including visual literacy. Yet, it has been unclear how secondary English/language arts teachers feel about the mandate to teach non-print literacy, if they understand what is expected of them in teaching non-print literacy, and if they indeed are teaching concepts related to comprehension and production of information in non-text format. This study attempts to discover teachers’ attitudes toward, understanding of, and use of visual literacy concepts through a survey of secondary English/language arts teachers in three counties in central Kansas. Based on the information from the responses to the survey, secondary English/language arts teachers in central Kansas have received little formal training in teaching visual literacy and that their informal training consists mainly of discussions with colleagues and independent study. Because they have received little training, most respondents see teaching visual literacy as secondary to teaching traditional literacy rather than as an integral part of such instruction. The state of Kansas has several standards relating to teaching non-print text. Yet, the emphasis on state and national tests is on print text. As a result, secondary English/language teachers surveyed know little about what it means to teach visual literacy. Training in how to incorporate visual literacy instruction with traditional literacy instruction, how to set outcomes for visual literacy and how to assess those outcomes are necessary if standards related to non-print text are to be addressed in secondary English/language arts classes across the state. While English/language arts pursue training in visual literacy on their own, teachers-preparatory institutions and public school systems also have a responsibility to see that English/language arts teachers know how to help their students become literate, not only in traditional literacies but also in non-traditional literacies such as visual literacy.
Keywords: visual literacy; English/language arts; Education, Curriculum and Instruction (0727)